Porous covalent triazine piperazine polymer (CTPP)/PEBAX mixed matrix membranes for CO2/N2 and CO2/CH4 separations - Thankamony, Roshni L.; Li, Xiang; Das, Swapan K.; Ostwal, Mayur M.; Lai, Zhiping (Journal of membrane science, 2019)
Mixed Matrix Membranes (MMMs) made from a porous covalent triazine piperazine polymer (CTPP) as filler embedded in poly ether-block-amide (PEBAX® 1657) were studied for the separation of CO2/N2 and CO2/CH4 gas systems. At a loading rate of 0.025 wt%, significant improvement was achieved for both CO2 permeability (from 53 to 73 barrer) and selectivity (from 51 to 79 for CO2/N2 and from 17 to 25 for CO2/CH4) that were measured at 293 K and 3 bars. Results of FTIR, DSC, WAXS, and SEM revealed a strong interaction between CTPP and PEBAX due to the high density of hydrogen bonding in CTPP, which led to chain rigidification of PEBAX at very low loading rate compared to other literature reported systems. On the other hand, CTPP contains rich nitrogen in the framework, which favourites the adsorption of CO2 more than N2 and CH4. Hence, although the chain rigidification decreased the CO2 adsorption sites in PEBAX matrix, the intrinsic porosity and high surface area of CTPP compensated the diffusivity and solubility which in turn improved the overall permeability and selectivity at a very low loading rate. CTPP is highly stable in acid, base, and high temperature up to 400 °C. Hence, this novel type material is a very promising filler for preparation of mixed matrix membranes for the separation of CO2/N2 and CO2/CH4 systems. [Display omitted] •MMMs prepared from a covalent porous polymer filler CTPP in polymer PEBAX.•Strong interactions between CTPP and PEBAX were discovered.•Multiple effects in CTPP/PEBAX MMMs were discovered.•Enhancement in both permeability and selectivity was achieved at very low loading.